The Influence of Family Controlled, Family Leadership and Profitability to Dividend Policy - Rochana, Anis; Wijayanto, Andhi (Universitas Negeri Semarang, 2018)
The aim of this study was to examine the effect of family controlled, family leadership and profitability towards dividend policy (study on familyfirmlisted on Indonesia Stock Exchange period 2012-2016). The population in this study was family company listed on Indonesia Stock Exchange period 2012-2016. The number of samples obtained based on purposive sampling technique as many as 20 companies. The Result of hypothesis test showed that family ownership had negative effect on dividend policy. Family member had negative effect on dividend policy. Family leadership had positive effect on dividend policy. Profitability had negative effect on dividend policy. So, it can be concluded that  firms which were led by CEOs who came from family member often tend to distribute dividends.